Development of hybrid coconut shell-peek adsorbent for methane adsorption: optimization using response surface methodology - Sidik, H. U. (Asian Research Publishing Network, 2017)
Adsorbed natural gas (ANG) provides efficient and clean combustion, with minimal emissions compared to diesel and gasoline. This article was designed to develop techniques of ANG for transportation application by apply RSM and CCD to identify the optimum preparation conditions for preparation of stable adsorbent for methane adsorption. Coconut shell and poly ether ketone (PEEK) was selected for synthesis of activated carbon (AC). The effectiveness of the parameters was determined using response surface method (RSM) couple with central composite design (CCD). The analysis of variance (ANOVA) was applied to identify the significant parameters. The quadratic model was adopted, as it has the highest F-value of 21.62 and P-value of less than 0.05, which relate the parameters and response. Microwave power has the highest F-value of 62.36. The maximum methane uptake of 5.12mmol g-1 was achieved. Overall, the hybrid coconut-PEEK adsorbent was found to be suitable for CH4 adsorption.